Media Pembelajaran Kitab Masailal Muhtadi Berbasis Multimedia - Azhar, Al; Iqbal, Muhammad; Najmuddin, Najmuddin; Azmi, Daril (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
This study is to develop a multimedia-based application for learning the scriptures using adobe flash cs 6 as a supporter for learning the scriptures. This study uses a research and development approach. The research site is at TPQ Zakiyatul Athfal Mane Tunong. The object of this research is the application of multimedia-based text book learning aids using macromedia flash. The method used in data collection was done through observation and interviews. The method used to analyze the data is descriptive qualitative analysis technique which is disclosed in the description. The feasibility test developed by the multimedia-based book learning tool application using macromedia flash is very feasible to use, because it can be used using an Android cellphone.